THE CONCEPT OF THE CONCEPTUAL PICTURE OF THE WORLD IN LINGUISTICS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2024)
This article explores the nature of conceptual images and their role in the development of our worldview. It examines how abstract conceptual images provide a foundation for image segmentation in the human mind. Additionally, the article investigates how language shapes mental imagery and how cultural differences influence our perceptions of the world. By delving into these topics, readers can better understand how conceptual images shape our worldview and affect communication across cultures.